A importância de um serviço qualificado de micologia em um hospital referência em doenças infectocontagiosas e dermatologia sanitária do Estado de Minas Gerais. - Vanessa Caroline Randi Magalhães (2020)
Eduardo de Menezes Hospital (HEM) is a reference hospital in infectious diseases and health dermatology. Located in the city of Belo Horizonte, it offers medical assistance to the entire state of Minas Gerais on an outpatient and hospital level, especially systemic mycoses. The present study was published in the mycology laboratory of the institution, which was without qualified technician responsible and with notifications from the Health Surveillance to be resolved. The mycology sector process started with a detailed situational analysis to identify possible that may be compromised, directly or indirectly, the performance of the mycological laboratory exams. The inconsistencies granted were listed and then grouped into four groups: structural, organizational, methodological and human resources (HR). Simultaneously, as notifications from the Health Surveillance (VISA) of the last eight years, directed to the sector studied, were updated and listed. Then, actions were defined to solve the different problems identified. The proposed objective was implemented and verified as a result of the interferences achieved: a qualified mycology service. The actions were based on a physical and procedural organization of the sector, preparation and updating of Standard Operating Procedures, internal flow standards, training, alignment with the multidisciplinary health team and the use and implementation of mycological laboratory techniques based on scientific evidence. In addition, an epidemiological study of mycological examinations was carried out, from 2014 to 2019, with the objective of identifying indicators that could quantify the result of the information technology process. A statistical analysis of the information enabled an improved assessment of the potential impact of the actions taken in the sector's IT process. Thus, it became evident that the structural, procedural and human resources organization, together with training programs and the use of methodologies based on scientific evidence, positively and significantly impact the final performance of the service provided. This study also made it possible to verify that the laboratory techniques used for the mycological diagnosis have limitations inherent to each methodology, and that the ideal is the use associated with them. In addition, alter the emergence of sporotrichosis with atypical disseminated manifestations.